Indigenous knowledge and values of organizational management for sustainable rural development in sri lanka - Yashoda, S.B. (university of Jaffna, 2014)
Utilization of Indigenous Knowledge as a source of sustainable development has become an increasingly discussed topic in past couple of years. Among many areas of indigenous knowledge, the attention given to “Organizational Management” is considerably low, even though the concept of management is acknowledged around the world as a means of achieving efficiency and effectiveness with scarce resources. Despite the Universal acceptability of the concept of management on “What” to do, the distinction of practices based on unique circumstances of different socio cultural backgrounds or “How” to do is strongly recognized in the contemporary management field. Being a developing country, Sri Lanka also needs a closer attention on sustainability of its development investments. With a heritage of a strong culture and deeply rooted shared values, there will be a potential of utilizing indigenous values of organizational management in ensuring a sustainable rural development. Thus, the aim of this study is to do a deep investigation on indigenous values embedded in organizational management practices existed in ancient Sri Lanka, with special reference to the geographical area of Nuwarakalaviya. Method adopted in this study associates with comprehensive review of primary and secondary data with qualitative data analysis tools. Strong and unique set of shared values could be identified with regard to work management, authority discharge and resource deployment; the main elements considered under organizational management. With the findings, some implications are proposed as appropriate to consider in contemporary rural development efforts for assuring sustainability through managing organizations successfully.
Keywords: Indigenous knowledge; Organizational management; Sustainable development